Port co-opetition: revisited after 20 years - Song, Dong-Wook; Deshmukh, Ajay (Taylor & Francis, 2026)
This paper revisits the concept of port co-opetition with the aim to understand how it has evolved over time since the publication 20 years ago. In so doing, the paper does also attempt to project its future research direction by synthesising the same concept applied to a wide range of academic disciplines. The first aim is of retrospective, while the second of prospective—looking for the future by looking back to the past. The study highlights that co-opetition, defined as doing both collaboration and competition at the same time, has seen noticeable changes over the past two decades by chasing the evolving nature of co-opetition within the port industry from actor-centric and activity-centric perspectives. The focus was initially on individual firms and their interactions; however, there has existed a greater emphasis on the broader activities and their processes as defined co-opetitive relationships. This shift reflects the general trend in the global economy where co-opetition has become increasingly relevant for players to successfully navigate ever more complicated market dynamics. Despite significant progress made in the field of port co-opetition, much of the existing literature remains cantered into the actor-centric view, having limitedly explored the other side of the concept. As a way to fill in this less considered perspective, this paper aims to propose a framework in which the port co-opetition per se could be more systematically analysed, leading us to gain a valuable insight into the field for the benefits of researchers and practitioners. This line of study will make us to better understand the concept in a context of port industry as a potential instrument of implementable strategies.
Keywords: Port co-opetition; dynamic framework; driver-process-outcome framework; actor-centric to activity-centric; strategic management; 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; Logistics & Transportation; 38 Economics; 44 Human society